An investigation into university EFL students’ and instructors’ perceptions of using a learning management system - Tayşı, Eda; Başaran, Süleyman (My University, 2018)
The aim of this study is to investigate Turkish EFL students’ and their instructors’ perceptions of using alearning management system (MyELT) in a blended learning context. The study was conducted at a stateuniversity with 129 preparatory class students, and 4 instructors of English. In order to collect data, a close –ended questionnaire was used. Semi-structured interviews were conducted with the instructors. While thequantitative data was analysed by means of SPSS, the qualitative data was analysed through content analysis.The results indicated that the students generally have positive perceptions about the practicality of MyELTthough they were not as sure about its usefulness. The findings showed no significant difference between maleand female students’ perceptions and between students who had easy and limited access to the internet.Similarly, no significant correlation was found between students’ perceptions and their average grade scores.Although the instructors believed in the pedagogical value of the MyELT, they regarded it unsuccessful in theirown context due to a number of reasons such as students’ lack of required ICT skills and some technical failures.
Keywords: Eğitim; Eğitim Araştırmaları; Dil ve Dil Bilim